(3QFjS eLdS GdhRQGA aj GdfXe GdHQdeGfjI GdeYGUQI (B/ s - (3eMeO bOQj MSfs; (3eMehO YGWa GdHfG (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1986)
(3JfbSe gPg GdQSGdI Edi KdGKI CHhGH; MjK jJfGhd GdHGH GdChd GNJjGQ QFjS eLdS GdhRQGA hGNJUGUGJg, hGdHGH GdKGfj jJfGhd YdGbI QFjS eLdS GdhRQGA HQFjS GdOhdI, hCNjQG GdHGH GdKGdK Yf YdGbI QFjS eLdS GdhRQGA HGdHQdeGfs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1986.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B441 - 470.s
Keywords: (3GdbGfhf GdOSJhQjs; (3GNJjGQ QFjS eLdS GdhRQGAs; (3GNJjGQ GdhRQGAs; (3GNJUGUGJ QFjS eLdS GdhRQGAs; (3GNJUGUGJ QFjS GdOhdIs; (3JahjV QFjS eLdS GdhRQGAs; (3Md GdHQdeGfs; (3GdQbGHI GdHQdeGfjIs; (3GdeSFhdjI GdSjGSjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs